DOI: 10.1007/978-3-540-73449-9_21
|View full text |Cite
|
Sign up to set email alerts
|

Proving Termination of Rewrite Systems Using Bounds

Abstract: Abstract. The use of automata techniques to prove the termination of string rewrite systems and left-linear term rewrite systems is advocated by Geser et al. in a recent sequence of papers. We extend their work to non-left-linear rewrite systems. The key to this extension is the introduction of so-called raise rules and the use of tree automata that are not quite deterministic. Furthermore, we present negative solutions to two open problems related to string rewrite systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In [17] we showed that deterministic tree automata-a common approach to handle non-linearity with automata techniques (cf. [3,18,19])-are unsuitable.…”
Section: Raise-dp-boundsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [17] we showed that deterministic tree automata-a common approach to handle non-linearity with automata techniques (cf. [3,18,19])-are unsuitable.…”
Section: Raise-dp-boundsmentioning
confidence: 99%
“…However as soon as we add those transitions again, they are removed since they cause A to be non-deterministic. In [17] we introduced quasi-deterministic tree automata to solve this problem. This carries over to the present setting without any problems.…”
Section: Raise-dp-boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Employing [16] (as in [5]) one sees that any match-raise bounded TRS has linear derivational complexity. Then the claim follows from Lemma 8 in [15].) Note that the restriction to non-duplicating TRS is harmless, as any duplicating TRS induces at least exponential derivational complexity.…”
mentioning
confidence: 91%
“…Clearly compatibility with strongly linear interpretations induces linear derivational complexity. Secondly, T T Tbox refers to the implementation of the matchbound technique as in [15]: Linear TRSs are tested for match-boundedness, nonlinear, but non-duplicating TRSs are tested for match-raise-boundedness. This technique again implies linear derivational complexity.…”
mentioning
confidence: 99%